Polymerase spiral reaction assay for rapid visual detection of Mycobacterium avium subsp. paratuberculosis in fecal samples - Vinod Kumar Singh; Vikas Gupta; Chayanika Das; Amit Kumar; Sharad K. Yadav (Scientific Reports)
Abstract A rapid, sensitive, and specific visual detection assay for Mycobacterium avium subsp. paratuberculosis (MAP) was developed and optimized using a polymerase spiral reaction (PSR) method. A pair of primers was designed targeting MAP specific sequence of IS900 putative transposes (p43) gene, and PSR results were assessed using agarose gel electrophoresis and colour change with SYBR Green-I dye. The assay was optimized using water bath and the optimum reaction time and temperature for MAP-PSR were 60 min and 64 °C, respectively. The sign of target amplification can be visualized by naked eyes as SYBR Green-I change its colour due to intercalation with amplified products. The developed assay demonstrated that the primers specifically detected MAP and showed no cross-reaction with other common Mycobacterium. The sensitivity of the PSR assay for MAP detection was 122 fg or ~ 23 copy number of the template. The MAP-PSR assay was also evaluated using 100 clinical samples, and a total 59 samples were found positive. When same samples were tested by conventional PCR, 50 samples were found positive, and all PCR positive clinical samples were found positive by MAP-PSR too. In conclusion the developed MAP–PSR assay is simple, rapid, specific, and sensitive, and thereby very suitable for application and promotion in the field and resource limited laboratories.